Crop detection technologies, mechanical weeding executive parts and working performance of intelligent mechanical weeding: a review - Xiang, Meiqi; Qu, Minghao; Wang, Gang; Ma, Zhongyang; Chen, Xuegeng; Zhou, Zihao; Qi, Jiangtao; Gao, Xiaomei; Li, Hailan; Jia, Honglei (Frontiers in Plant Science, 2024)
Weeding is a key link in agricultural production. Intelligent mechanical weeding is recognized as environmental friendly, and it profoundly alleviates labor intensity compared with manual hand weeding. While intelligent mechanical weeding can be implemented only when a large number of disciplines are intersected and integrated. This article reviewed two important aspects of intelligent mechanical weeding. The first one was detection technology for crops and weeds. The contact sensors, non-contact sensors and machine vision play pivotal roles in supporting crop detection, which are used for guiding the movements of mechanical weeding executive parts. The second one was mechanical weeding executive part, which include hoes, spring teeth, fingers, brushes, swing and rotational executive parts, these parts were created to adapt to different soil conditions and crop agronomy. It is a fact that intelligent mechanical weeding is not widely applied yet, this review also analyzed the related reasons. We found that compared with the biochemical sprayer, intelligent mechanical weeding has two inevitable limitations: The higher technology cost and lower working efficiency. And some conclusions were commented objectively in the end.